Hubungan Gaya Hidup dengan Kejadian Hipertensi pada Petani di Wilayah Kerja Puskesmas Panti Kabupaten Jember - Animas Debby Sugesti Andriani; Hanny Rasni; Tantut Susanto; Latifa Aini Susumaningrum; Slamet Siswoyo (Poltekkes Kemenkes Banjarmasin, 2021)
Unhealthy lifestyle among farmers contributed a risk for increasing blood pressures. The aim of this study was to analyze the relationship between lifestyle and the incidence of hypertension among farmers in public health services of Panti, Jember Regency. A cross-sectional study was conducted among 248 farmers using stratified random sampling. A self-administered questionnaire was used to measure sociodemographic of farmers, lifestyles questionnaire, while sphygmomanometer was measured blood pressure. Chi Square test was used to analyze the relationship between lifestyle and incidence of hypertension. This study found that lifestyle of farmers were 52.4% of moderate physical activity, 59.3% of no smoking, 61.2% of sodium consumption, and 59.3% of no stress. Meanwhile, the incidence of hypertension was 39,5% of systolic prehipertension and 33.5% of normal diastolic. There were significantly relationship between physical activity (X2 = 75,657 and P-value= <0,001), smoking (X2= 18,621 and P-value= <0.001), sodium consumption (X2= 13.291 and P-value= 0,039), stress (X2= 44,386 and P-value= <0.001) and the incidence of hypertension in systolic blood pressure. The relationship between physical activity (X2= 43,002 and P-value= <0,001), smoking (X2= 25.702 and P-value= <0.001), sodium consumption (X2= 12.541 and P-value= 0,014), stress (X2= 36,378 and P-value= <0.001)and the incidence of hypertension in diastolic blood pressure. The conclusion of this study, there are relationship between lifestyle and incidence of hypertension. Therefore, farmers could modify their lifestyle to maintain a blood pressure.